AN ANALYSIS STUDENTS’ ABILITY IN USING PAST TENSE OF TENTH GRADE AT SMK SWASTA MULIA PRATAMA MEDAN - Ria Monalisa Simanjuntak; Sri Ninta Tarigan (Universitas Suryakancana, 2020)
The aim of the researcher is to know the students’ ability in use simple past tense of Tenth Grade at SMK Swasta Mulia Pratama Medan. The method of this research is a case study in the form qualitative research method. The total samples of this research are 24 students. The researcher analyzed the data by multiple choice test. The result show that the mean score of students 27,95. The students were belonged into weak category gained by 12 student (50%). The other students were belonged into very good category gained 2 students (8%). The other students were belonged category fair 3 students (12%). 7 students (30%) who belonged to poor category. The students still do not understand and confuse about simple past tense, but some of them can able to answer the test very well because they are more learn and already know about past tense. And some of them could not able to answer the test is because they really do not know about simple past tense.